Do Low Rents in Jakarta’s Rusunawa Program Improve Housing Affordability for Low Income Households? - Muh Azis Muslim; Kania Falahiatika Hidayat (Department of Public Administration, 2026)
Rumah Susun Sederhana Sewa (Rusunawa) is a major public housing program for low-income communities in Jakarta. However, the accumulation of rent arrears—reaching IDR 95.5 billion between 2010 and 2025—raises critical concerns about its ability to ensure housing affordability. This study adopts a qualitative approach using secondary data with two main objectives: first, to assess housing affordability from a residual income perspective as experienced by residents, considering not only housing costs but also post-occupancy costs and broader housing attributes; and second, to examine whether persistent rent arrears reflect structural affordability constraints and, consequently, a form of policy failure. The findings show that low rental prices do not guarantee affordability. Rent-setting mechanisms fail to account for income instability and socioeconomic heterogeneity, while post-occupancy stress—arising from livelihood disruption and increased transportation costs—further erodes residents’ residual income. As a result, persistent rent arrears reflect structural affordability constraints rather than tenant non-compliance, highlighting a misalignment between policy design and residents’ lived economic realities. These findings suggest the need for differentiated rent-setting mechanisms based on household characteristics, alongside strengthened housing pathway support to facilitate transitions into private rental housing or homeownership.